2002
DOI: 10.1046/j.1365-2168.2002.02188.x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous tumour rupture and prognosis in patients with hepatocellular carcinoma

Abstract: The presence of sudden-onset abdominal pain is the only independent indicator of ruptured HCC. Hepatic resection, when feasible, is the treatment of choice and can result in an overall survival rate comparable to that of patients with non-ruptured HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
102
4
6

Year Published

2003
2003
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(124 citation statements)
references
References 8 publications
12
102
4
6
Order By: Relevance
“…Our findings also suggest that interaction between VEGF and Ang2 may play a critical role in tumor angiogenesis in HCC. Hepatocellular carcinoma (HCC) is a highly vascular tumor, and this increased vascularity can lead to tumor rupture (1). Angiogenesis, formation of new microvessels, is critical for the growth and progression of various human solid tumors because it enables delivery of oxygen and nutrients (2).…”
Section: Hepatocellular Carcinoma (Hcc) Is Becoming One Of the Most Cmentioning
confidence: 99%
“…Our findings also suggest that interaction between VEGF and Ang2 may play a critical role in tumor angiogenesis in HCC. Hepatocellular carcinoma (HCC) is a highly vascular tumor, and this increased vascularity can lead to tumor rupture (1). Angiogenesis, formation of new microvessels, is critical for the growth and progression of various human solid tumors because it enables delivery of oxygen and nutrients (2).…”
Section: Hepatocellular Carcinoma (Hcc) Is Becoming One Of the Most Cmentioning
confidence: 99%
“…Tumors characterized by progressive growth and/or subglissonian locations are at high risk for rupture [1]. In areas like Asia or Africa, where the incidence of HCC is high, rupture is a common presenting symptom (11-26 % as compared to 2-3 % of cases diagnosed in Spain and Italy) [2][3][4].…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…Liu et al [15] concluded that survival after two-stage liver resection post-HCC rupture was inferior compared to patients who did not have this complication, whereas Yeh et al [17] found that ruptured HCC had similar overall survival rates compared to non-ruptured HCC but inferior disease-free survival rates. Mizuno et al [18] noted that there was no difference in overall survival between ruptured and non-ruptured HCC.…”
Section: [16]mentioning
confidence: 99%